Measurement of the branching ratio related to the internal pair production of Y-90. (February 2020) - Dryák, Pavel; Šolc, Jaroslav
Abstract: The aim of the work is to determine the number of positron-electron pair creation in the E0 transition between the 1760.7 keV level and the ground level of the Zr-90 nucleus at the Y-90 decay. The number of conversions is determined from the number of 511 keV photons originating from positron annihilation corrected for the annihilation of positrons in flight. Emission of annihilation photons was determined from the measurements of 511 keV full-energy peak on two calibrated high-purity germanium detectors. The measurements were performed with two sources of a different construction. The first source was a 1 ml ampoule filled with Sr-90 solution (in equilibrium with Y-90) with an activity of 38.041 MBq inserted into an aluminum absorber. The other source was the evaporation residue of the Sr-90 solution (in equilibrium with Y-90) in a polyethylene absorber. In both cases, the annihilation of positrons occurred in the source materials. The efficiency of 511 keV photon detection was determined by Monte Carlo calculation, where the source was defined as a theoretical continuous positron spectrum with a maximum energy of 738 keV. The branching ratio related to the internal pair production during Y-90 decay was determined to be (3.26 ± 0.04) × 10 -5 pairs/decay. Highlights: New evaluation of Y-90 internal pair production intensity and number of 511 keV pairs. Two different Sr-90/Y-90 sources used, each measured on two different HPGe detectors. Y-90 internal pair production intensity determined to be (3.26 ± 0.04) × 10 -5 pairs/decay. The number of photon pairs with the energy 506–515 keV determined to be (3.21 ± 0.04) × 10 -5 pairs/decay.